Equality Strategy for Reducing Stunting Prevalence Rate: Case Study of DKI Jakarta Province (Jurnal Bina Praja, 2023)
This research aims to explore strategies for reducing the stunting prevalence rate in DKI Jakarta Province, which has reached 14.8 percent. The stunting rate is a problem because the DKI Jakarta governor's target for 2024 is to hope that the stunting rate will be more evenly distributed to reach the national target of 14 percent. The research hypothesis is how the DKI Jakarta Province's stunting prevalence rate will be evenly distributed throughout the region. The highest figure was in Seribu Islands Regency, around 20.50 percent; the lowest was in South Jakarta, around 11.90 percent; and the cities of East Jakarta and Central Jakarta were 14 percent. The research methodology uses qualitative methods with descriptive research design. Research data was taken from interviews in the field. By taking a population of stunting participants from four regions in DKI Jakarta, 20 people each, so the total sample is 100 people. The research results show that the two decisions of the Governor of DKI Jakarta, Number 981 and 774 of 2022, have been effective and right on target in overcoming the reduction in the prevalence of stunting rates. It's just that a more equitable strategy for reducing stunting prevalence rates is needed relatively evenly throughout the DKI Jakarta area. In conclusion, DKI Jakarta Province has reduced the stunting prevalence by 14.8 percent. A comprehensive strategy is needed to reduce the prevalence of stunting evenly, namely: (1) making a Regional Regulation for the DKI Jakarta Province regarding stunting; (2) increasing the number of Foster Fathers for Stunting Children (BAAS) from entrepreneurs and other stakeholders so that the stunting reduction strategy reaches the target of 14 percent evenly.
Keywords: reduction strategy; stunting prevalence rate